2012
DOI: 10.1155/2012/953459
|View full text |Cite
|
Sign up to set email alerts
|

Antiallodynic Effect of Herbal Medicine Yokukansan on Peripheral Neuropathy in Rats with Chronic Constriction Injury

Abstract: Yokukansan, one of the traditional Japanese herbal medicines, ameliorated neuropathic pain symptoms in patients. In this study, we investigated the effects of yokukansan on neuropathic pain in chronic constriction injury (CCI) model. Oral administration of yokukansan significantly inhibited mechanical and cold allodynia in the von Frey hair or acetone test, respectively. In comparison, amitriptyline, a tricyclic antidepressant, demonstrated moderate, but not significant, antiallodynic effects in the mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Although the mechanisms underlying the inhibition of morphine tolerance by YKS have not been determined, the role of the noradrenergic system in the development of morphine tolerance appears to be minimal (Dossin et al, 1996;Ö zdog˘an et al, 2004). Although we cannot fully exclude the possibility that a 2 -AR is involved in the attenuation of morphine tolerance by YKS, we consider that other mechanisms, such as the modulation of glutamatergic system by YKS (Trujillo and Akil, 1991;Takeda et al, 2008;Kawakami et al, 2009Kawakami et al, , 2011Suzuki et al, 2012), may be involved instead.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the mechanisms underlying the inhibition of morphine tolerance by YKS have not been determined, the role of the noradrenergic system in the development of morphine tolerance appears to be minimal (Dossin et al, 1996;Ö zdog˘an et al, 2004). Although we cannot fully exclude the possibility that a 2 -AR is involved in the attenuation of morphine tolerance by YKS, we consider that other mechanisms, such as the modulation of glutamatergic system by YKS (Trujillo and Akil, 1991;Takeda et al, 2008;Kawakami et al, 2009Kawakami et al, , 2011Suzuki et al, 2012), may be involved instead.…”
Section: Discussionmentioning
confidence: 91%
“…The expression of a 2A -AR was similarly prevented by yohimbine, a specific a 2A -AR antagonist, as well as by active YKS constituents, including GRderived glycyrrhizin and UH-derived GME. Recent evidence suggests that YKS can attenuate neuropathic pain in human patients ) and chronic constriction injury-induced neuropathic pain in animals (Suzuki et al, 2012). Given the increasing use of opioids for the relief of chronic non-cancer-associated pain such as neuropathic pain, the concomitant administration of YKS with opioids may be useful in long-term therapy for chronic pain patients to reduce opioid tolerance and physical dependence.…”
Section: Resultsmentioning
confidence: 99%
“…YKS is sometimes effective in clinical practice for ameliorating neuropathic pain symptoms and another paper reports on YKS’s pain-relieving effect, validating such clinical efficacy in a rat chronic constriction injury model 38. YKS significantly inhibited mechanical and cold allodynia in the von Frey hair or acetone test, respectively, while amitriptyline, a tricyclic antidepressant, demonstrated moderate, but not significant, antiallodynic effects in the same tests.…”
Section: Animal Studiesmentioning
confidence: 84%
“…Uchida et al,11 reported a stress load consistent with that of the current study and that 300 mg/kg of YKS was effective. In other experiments, YKS was administered at the upper limit of 1,000 mg/kg 14,15,20,21. In this study, we orally administered these two doses once each day.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it ameliorates sleep disorders24,25 and cognitive dysfunctions;29 acts as a neuroprotective agent,30 and induces neuronal differentiation 31. YKS is also an analgesic21,22,32 that prevents the development of morphine tolerance,33 and it acts as an antipruritic34 and inhibits allergic responses34 and dyskinesia 23…”
Section: Discussionmentioning
confidence: 99%